RAC1 activation mediates Twist1-induced cancer cell migration - Yang, Wen-Hao; Lan, Hsin-Yi; Huang, Chi-Hung; Tai, Shyh-Kuan; Tzeng, Cheng-Hwai; Kao, Shou-Yen; Wu, Kou-Juey; Hung, Mien-Chie; Yang, Muh-Hwa (Nature cell biology, 2012)
Epithelial–mesenchymal transition (EMT), which is characterized by the suppression of the adhesion protein E-cadherin, is a crucial process that promotes metastasis and stem-like properties of cancer cells. However, the dissociation of cellular aggregates is not sufficient to explain why cancer cells move, and the motile nature of cancer cells undergoing EMT remains elusive. Here, we identify a mechanism in which the EMT inducer Twist1 elicits cancer cell movement through activation of RAC1. Twist1 cooperates with BMI1 to suppress let-7i expression, which results in upregulation of NEDD9 and DOCK3, leading to RAC1 activation and enabling mesenchymal-mode movement in three-dimensional environments. Moreover, the suppression of let-7i contributes to Twist1-induced stem-like properties. Clinically, activation of the Twist1– let-7i –NEDD9 axis in head and neck cancer patients correlates with tumour invasiveness and worse outcome. Our results uncover an essential mechanism to explain how Twist1 induces the motile stem-like cancer cell phenotype beyond simply suppressing E-cadherin. Yang and colleagues delineate a pathway that controls cell migration in 3D environments following Twist1-mediated epithelial-to-mesenchymal transition. They show that Twist1 represses the let-7i microRNA, leading to upregulation of the RAC1-activating factors NEDD9 and DOCK3, and inducing mesenchymal-mode motility and tumour invasion in vivo .